(Invited) Synchrotron White-Beam X-Ray Topography Analysis of the Defect Structure of HVPE-GaN Substrates. (13th April 2015) - Kirste, Lutz; Danilewsky, Andreas N.; Sochacki, Tomasz; Köhler, Klaus; Zajac, Marcin; Kucharski, Robert; Boćkowski, Michal; McNally, Patrick J.
Abstract : The defect structure of HVPE-GaN crystals are examined using synchrotron white-beam X-ray topography (SWXRT) and topography results are interpreted and discussed in comparison to reciprocal lattice point broadening from high resolution X-ray diffraction (HRXRD) measurements. Two as-received commercial HVPE-GaN wafers from two different vendors and one HVPE-GaN which was grown on an ammonothermal GaN-seed are investigated in this study. From large-area topography the formation of a cellular defect network is identified for the commercial HVPE-GaN. Large differences in the crystal lattice misorientation deformation (mosaicity) are determined for the different samples by transmission section topography. For the HVPE-GaN grown on an ammonothermal GaN-seed a very low defect density was ascertained. From the contrasts of the topography threading screw-type dislocations and threading mixed-type dislocations were identified. The structure analyses show that the outstanding structural properties of the ammonothermal GaN-seed are adopted by the HVPE-GaN.